Competing events and costs of clinical trials: Analysis of a randomized trial in prostate cancer. Issue 1 (April 2015) - Zakeri, Kaveh; Rose, Brent S.; D'Amico, Anthony V.; Jeong, Jong-Hyeon; Mell, Loren K.
Abstract Background Clinical trial costs may be reduced by identifying enriched subpopulations of patients with favorable risk profiles for the events of interest. However, increased selectivity affects accrual rates, with uncertain impact on clinical trial cost. Methods We conducted a secondary analysis of Southwest Oncology Group (SWOG) 8794 randomized trial of adjuvant radiotherapy for high-risk prostate cancer. The primary endpoint was metastasis-free survival (MFS), defined as time to metastasis or death from any cause (competing mortality). We used competing risks regression models to identify an enriched subgroup at high risk for metastasis and low risk for competing mortality. We applied a cost model to estimate the impact of enrichment on trial cost and duration. Results The treatment effect on metastasis was similar in the enriched subgroup (HR, 0.42; 95% CI, 0.23–0.76) compared to the whole cohort (HR, 0.50; 95% CI, 0.30–0.81) while the effect on competing mortality was not significant in the subgroup or the whole cohort (HR 0.70; 95% CI 0.39–1.23, vs. HR 0.94; 95% CI, 0.68–1.31). Due to the higher incidence of metastasis relative to competing mortality in the enriched subgroup, the treatment effect on MFS was greater in the subgroup compared to the whole cohort (HR 0.55; 95% CI 0.36–0.82, vs. HR 0.77; 95% CI, 0.58–1.01). Trial cost was 75% less in the subgroup compared to the whole cohort (1.7 million vs. 6.8 million), and the trial duration was 30% shorter (8.4 vs. 12.0 years). Conclusion Competing event enrichment can reduce clinical trial cost and duration, without sacrificing generalizability.